Radio Within and Across Borders. Music as national and international in interbellum Danish radio: Special section: RadioMusic. Papers from the LARM conference ‘Digital Archives, Audiovisual Media and Cultural Memory’ Copenhagen, 14–15 November 2013 - Michelsen, Morten (Danish Yearbook of Musicology, 2016)
Politically, Europe was dominated by both renewed national movements and tendencies towards internationalism in the decades following World War I. As a new and strong medium, radio became a tool for supporting nation-building in individual countries and for developing international relations, for example through the International Broadcasting Union (IBU). In this article I look at this apparent paradox by investigating a few aspects of the Danish music repertoire and the principles for radio transmission. I demonstrate how the Danish Broadcasting Corporation (DR) practised both principles in their programming without seeing it as a problem in any way. The enormous amount of music, which radio made it possible to listen to, contributed to this – not least because the music always became more or less contextualized thanks to radio’s many metatexts. In this way music in early radio contributed to a certain understanding of the modern, the ‘other’, and the new, making them less strange. At the same time radio articulated a well-known, ‘homely’ music background as the basis for understanding the new.